EVALUASI IMPLEMENTASI BALANCED SCORECARD STUDI KASUS PT BUKIT ASAM (Persero) Tbk - , RACHMAT DARMA PUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Performance measurement an important aspect nowadays for companies competing in the business. Economics globalization and technological development are challenges for all companies, especially those aimed at generating profits. In order to survive in the competition, every company should be able to measure performance in order to determine the appropriate strategies and allocate resources properly. Balanced Scorecard is a system used to measure the performance of the balance of financial and non-financial performance measurement. PT Bukit Asam (Persero) Tbk is a state-owned company engaged in coal mining and energy, has implemented Balanced Scorecard as a measure of performance and management strategies. In the implementation of the Balanced Scorecard evaluation is needed to ensure the Balanced Scorecard run in accordance with the company's goals. Researcher used The Principles of Strategy Focused Organization or Strategy Focused Organization Principles by Kaplan & Norton in developing research. From the research conducted, PT Bukit Asam (Persero) Tbk have met principle Strategy Focused Organization, but there are some things that should be improved, such as individual Balanced Scorecard management for employees, so the use of the Balanced Scorecard can be optimized.